Pendekatan Matematika Realistik (PMR) Dalam Meningkatkan Prestasi Belajar Matematika Siswa Kelas V SD Negeri 17 Parepare - Zaid Zainal (Publikasi Pendidikan, 2017)
The aims of this research to determine the learning outcome math class V students of SD Negeri 17 Parepare using the approach Realistic Mathematics (PMR). The research used qualitative descriptive and type of research is the Classroom Action Research (PTK) cyclical which includes planning, implementation, observation, and reflection. The subjects of this research were fifth grade students of SD Negeri 17 Parepare, in the first semester of academic year 2016/2017 with 30 students. The experiment was conducted on two cycles, the first cycle during the 4 meetings and the second cycle during the 4 meetings. Data was collected using achievement test at the end of the first cycle and the end of the second cycle and by using observation sheet and questionnaire responses of students. The results of quantitative analysis showed that the average score of the mathematics learning outcomes Elementary School fifth grade students at the end of cycle 17 Parepare I was in the moderate category. At the end of the second cycle, the average score of students' mathematics learning outcomes at the high category. Qualitatively, there is increased presence and activity of students in learning. Based on these results it can be concluded that with the implementation of realistic mathematics approach can improve mathematics achievement fifth grade students of SD Negeri 17 Parepare.Keywords: Realistic Mathematics Education, Achievement